Fault-Tolerant Controllers in Robotic Manipulators. Performance Evaluations - Urrea-Onate, E; Kern-Molina, J (2013)
In this paper performance evaluation of three fault-tolerance controllers based on the following control techniques: hyperbolic sine and hyperbolic cosine, calculated torque, and adaptive inertia; applied to manipulator robots is presented. Various tests are developed in a simulation environment, which is developed by employing MatLab/Simulink programming tools, when the manipulator must follow a desired trajectory and one of its actuators is locked. The results are obtained by means of curves and rms index of joint and Cartesian errors for each controller. © 2003-2012 IEEE.